МУҲАММАДНИЁЗ НИШОТИЙНИНГ “ҲУСН-У ДИЛ” ДОСТОНИ ВА КУБРАВИЙЛИК ТАЪЛИМОТИДАГИ “ЎН УСУЛ” ҲАМДА РАНГЛАР ТАЛҚИНИ - Аметова, У.К. (SCIENCE and SOCIETY, 2021)
Philosophical thoughts and moral views in Muhammadniyaz Nishoti’s epic "Husn-u Dil" of collection are interconnected with the ideas of N.Kubro’s creativity. The first similarity in their works is that there is an improvement in divine desire and divine beauty, the moral of the person. In addition, in their artistic treasures, they carry a correspondence with mysticism.